Bezirk Charkov, Ukraine. Die Infrastruktur im Gebiet der Dnepr-Severskij Donec-Wasserscheide in spätrömischer Zeit und zu Beginn der Völkerwanderungszeit - Schultze, Erdmute (e-Forschungsberichte des DAI, 2017)
The research in close co-operation with the Ukrainian partner devoted to settlement history of the 4th and 5th century AD in the modern district of Kharkiv (East Ukraine) has been continued in 2015–16. In the vicinity of Voitenki, the settlement and the cemetery of the Chernyakhov culture are excavated with a focus on landscape archaeology. Recent surveys confirmed that in the 4th century this settlement spread on both sides of a small water course and had probably a larger extension than expected before. At the cemetery until now 215 graves have been excavated consisting of 109 cremations, 105 inhumations and one cenotaph. New instructing material for comparison to this huge necropolis has been found in Zachepilovka in the southern part of Kharkiv district where rescue excavations are conducted by the co-operation partner in a cemetery of the Chernyakhov culture.